Synthesis and properties of crown ether functionalized coumarin substituted zinc phthalocyanine - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The novel 6,7-[15-crown-5]-3-[p-(2,3-dicyanophenoxy)phenyl]coumarin (1) and its non-peripherally substituted zinc phthalocyanine complex (2) have been prepared and characterized by elemental analysis, H-1 NMR (for compound 1), MALDI-TOF, FT-IR and UV-Vis spectral data. Fluorescence intensity changes of compound 1 have been determined by addition of Na+ or K+ ions at 25 degrees C in THF. The effects of the chromenone crown ether substituent of the phthalocyanine molecule on the photophysical (fluorescence quantum yield and lifetime) and photochemical (singlet oxygen generation and photodegradation) properties were also investigated. The fluorescence of the zinc phthalocyanine complex is effectively quenched by addition of 1,4-benzoquinone (BQ). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Crown ether; Phthalocyanine; Fluorescence; Singlet oxygen; Quantum yield; PHOTOCHEMICAL PROPERTIES; PHOTODYNAMIC THERAPY; PHOTOPHYSICAL PROPERTIES; COPPER PHTHALOCYANINE; QUANTUM YIELDS; GAS SENSOR; DERIVATIVES; PHOTOSENSITIZERS; SOLVENTS; MOIETIES